The relationship between sleep disturbance and obsessive– compulsive symptoms: the mediation of repetitive negative thinking and the moderation of experiential avoidance - Zhao, Xudong; Shen, Liao; Pei, Yufei; Wu, Xiaojun; Zhou, Ningning (Frontiers in Psychology, 2023)
Background: Studies have found that sleep disturbance is associated with obsessive-compulsive symptoms. This study aimed to elaborate on the mediating and moderating mechanisms between these two variables. We hypothesized that repetitive negative thinking plays a mediating role in the relationship between sleep disturbance and obsessive-compulsive symptoms, and experiential avoidance plays a moderating role. Method: This study included 639 Chinese adults. A questionnaire survey was used to assess sleep quality, obsessive-compulsive symptoms, experiential avoidance, repetitive negative thinking, and depression symptoms. A moderated mediation model was established. Results: After controlling for depressive symptoms, repetitive negative thinking partially mediated the positive correlation between sleep disturbance and obsessive-compulsive symptoms. This indirect relationship was significant in individuals with lower experiential avoidance levels. Particularly, the relationship between sleep disturbance and repetitive negative thinking was significant among individuals with lower experiential avoidance levels, but not among individuals with higher experiential avoidance levels. Conclusion: This study demonstrated that repetitive negative thinking partially mediated the impact of sleep disturbance on obsessive-compulsive symptoms. The findings suggest that when providing support to individuals with sleep disturbance and obsessive-compulsive symptoms, assessing their level of experiential avoidance is necessary for performing targeted interventions. Individuals with low experiential avoidance may benefit from a clinical intervention targeting repetitive negative thinking to improve sleep quality and obsessive-compulsive symptoms.